Konfrontasi Kerajaan Franka terhadap Dinasti Umayyah II di Andalusia Tahun 777-814 M - Purnama, Agung (Historia Madania: Jurnal Ilmu Sejarah, 2020)
In the 8th and 9th centuries AD, the geopolitics of Western Europe was characterized by two major powers with different religious backgrounds. The Frankish Kingdom is centered in Aachen Germany which is the kingdom of the Christians, Umayyad Dynasty II in Cordoba, Andalusia, center of Islamic civilization in Europe. This paper reveals the patterns of interaction between the two kingdoms, using four stages of historical research methods in the form of heuristics, criticism, interpretation, and historiography. The heuristic is done by means of literature study and literature review. The results showed that the Frankish Kingdom carried out a confrontation through a series of military campaigns and invasions of areas in the Iberian Peninsula controlled by the Umayyad II Dynasty. The invasion, that was carried out by the Frankish Kingdom, received support from the Abbasid Dynasty in Baghdad which was the enemy of the Umayyad Dynasty. However, this invasion failed. Keywords : Confrontation, Charlemagne, Frankish Kingdom, Umayyad Dynasty II, Andalusia